Ocular Features in Patients with Ocular Tuberculosis - Nabil Bahran; Nur Aulia; Pither Sandy; Edward Pandu Wiriansyah; Ratih Natasha Maharani (International Medical Journal Corp. Ltd, 2025)
Background: Tuberculosis (TB) is a significant global health problem, infecting millions of people each year and being one of the deadliest infectious diseases. The term ocular tuberculosis describes an infection by Mycobacterium Tuberculosis species that can affect any part of the eye (intraocular, superficial, or surrounding the eye), with or without systemic involvement. Objective: To review the ocular features in patients with ocular tuberculosis through a review of current literature. Methods: This study is a narrative review of 7 scientific articles published between 2020–2025, with searches conducted through Google Scholar, PubMed, and other databases using the keywords